Occurrence and identification of Emeria species in broiler rearing under traditional system. Issue 1 (December 2015) - Shamim, Asim; ul Hassan, Murtaz; Yousaf, Arfan; Iqbal, Muhammad; Zafar, Muhammad; Siddique, Rao; Abubakar, Muhammad
Abstract Background The present study was intended to determine the prevalence and identification of species involved causing coccidiosis in broilers rearing under traditional farming system in Mirpur, Azad Kashmir, Pakistan. For the current study, a convenient sampling technique was carried out. A total of 7814 broilers (aged 1 to 6 weeks) were submitted to the Disease Diagnostic Laboratory of Livestock and Animal husbandry Department Mirpur, Azad Kashmir. Results From the total screened, 750 were found positive for coccidiosis representing an overall prevalence of 9.59 %. Age-wise highest prevalence (10.88 %) recorded in the middle age birds (0 to 3 week old) were found more susceptible to infection than those aged above 3 weeks. Higher prevalence (12.49 %) of coccidiosis in broilers was observed in spring as compared with 6.60 % in summer season. In this study two main coccidiosis causing species, Emeria tenella andEmeria maxima were identified on the basis of their morphological feature and habitat (caeca and intestine), However, E. tenella was dominant compared toE. maxima . Conclusion The study provides an insight to the occurrence ofEmeria species which must be taken into consideration when rearing the broilers.